IMPLEMENTASI ETIKA BISNIS ISLAM DALAM PEMASARAN - Jumi Atika (Institut Agama Islam Negeri Padngsidimpuan, 2016)
Business ethics is a study devoted about moral right and wrong. So the need to see how the ethics in advertising and marketing so that no negative impact on the environment . Business ethics of Islam in marketing offers the concept of 4P + 2P, and ethics in advertising must be ethical, aesthetic and artistic so that the ads can make shoppers drool and do not feel deceived and Strategy Umar Allaah anhu in protecting the environment is based on the fundamentals of the faith and the rules morals that govern the behavior of a Muslim in the life and combat a buse so that no negative impact on the environment.